A Comparative Analysis of Renewable Energy Policies and its Impact on Economic Growth: A Review - Eze, Val Hyginus Udoka; Edozie, Enerst; Wisdom, Okafor; Uche, Chikadibia Kalu Awa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Renewable energy has been identified as a critical component of global efforts to address climate change, enhance energy security, and foster sustainable economic growth. As a result, many countries have implemented renewable energy policies to promote the development and deployment of renewable energy technologies. However, the impact of these policies on economic growth remains a subject of debate. This article provides a comparative analysis of renewable energy policies and their impact on economic growth. The study employs a systematic review of the literature and utilizes qualitative and quantitative methods to compare renewable energy policies and their economic impacts across different countries. The findings suggest that the impact of renewable energy policies on economic growth varies across countries and is influenced by factors such as policy design, institutional context, and economic structure. This research article finally, examined the challenges associated with implementing renewable energy policies, analyzed the implications of the findings for policymakers and further gave some potential solutions that will help the policymakers and future researchers.